Morphogenesis of Stigmatella aurantiaca fruiting bodies. - Vasquez, G M (1985)
Scanning electron micrographs of intermediate stages of fruiting body formation in the myxobacterium Stigmatella aurantiaca suggest that fruiting body formation can be divided into several stages distinguishable on the basis of the motile behavior of the cells. Aggregates formed at sites where cells glide as groups in circles or spirals. Thus, each aggregate was surrounded by a wide band of cells. Several streams of cells were pointed toward and connected to the wide band of cells at the base of the aggregate, suggesting directed cell movement toward the aggregate. The pattern of cells at the base of taller, more mature aggregates suggested that groups of cells enter the aggregate from the surrounding band of cells by changing the pitch of their movement, thus creating an ascending spiral. Stalk formation was characterized by a distinctly different pattern, which suggested that single cells emerge from the band of cells and move toward the aggregate, under it, and then vertically to create the stalk. At this stage, the aggregate appeared to be torn from the substrate as it was lifted off the surface. The cells in the completed stalks were well separated, and most had their long axes pointed in a vertical direction. A great deal of the stalk material appeared to be slime in which the cells were embedded and through which they were presumably moving in the live material. Some suggestions regarding factors that may direct the observed morphogenetic movements are discussed.